Product and Price as Key Drivers of Customer Loyalty in Modern Retail: A Case Study of Alfamidi in Ambon - Farida Mony; Reza Abdulmudy (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of the marketing mix, consisting of product, price, place, and promotion, on customer loyalty at Alfamidi located at the Perempatan Kebun Cengkeh intersection, Ambon City. This research employs a quantitative approach with an associative-causal design. A sample of 50 respondents was obtained through accidental sampling technique. Data were collected using a five-point Likert scale questionnaire and analyzed using multiple linear regression with SPSS. The results indicate that partially, product and price have a positive and significant effect on customer loyalty, while place and promotion do not have a significant effect. However, simultaneously, all four marketing mix variables collectively exert a significant influence on customer loyalty, with an Adjusted R Square value of 45.8%. These findings suggest that in the context of modern retail in Ambon, consumers prioritize product variety and affordable pricing as the primary drivers of loyalty, rather than physical location and promotional activities. This study provides implications for retail management to focus their strategies on strengthening product offerings and competitive pricing to sustain customer loyalty in an increasingly saturated market.